2019
DOI: 10.1111/gcb.14787
|View full text |Cite
|
Sign up to set email alerts
|

Zones of influence for soil organic matter dynamics: A conceptual framework for data and models

Abstract: Soil organic matter (SOM) is an indicator of sustainable land management as stated in the global indicator framework of the United Nations Sustainable Development Goals (SDG Indicator 15.3.1). Improved forecasting of future changes in SOM is needed to support the development of more sustainable land management under a changing cli-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 115 publications
(127 reference statements)
1
17
0
Order By: Relevance
“…Under low-to-moderate vegetation biomass cover (<5 kg m −2 vegetation water content), the L-band (1.4 GHz) Tb observations are especially sensitive to the dielectric properties, including moisture levels, within the surface soil layer (Entekhabi et al, 2010), which is congruent with the 0-to 5-cm surface soil layer depth of the SMAP L4SM product. This is also consistent with the L4C calibration against flux tower observations, as the surface soil layer generally encompasses more recent and labile SOC, which generally contributes the largest component of the soil RH flux (Bond-Lamberty et al, 2004) and is more sensitive to seasonal and interannual climate variability (Cagnarini et al, 2019;Chen et al, 2013) relative to deeper soil layers. The accuracy of L4SM soil moisture estimates is lower in areas of dense vegetation and areas where precipitation gauge measurements are sparse , due to uncertainty in the Tb assimilation and the Catchment land model, respectively.…”
Section: Data Sources 211 Smap L4c Surface Socsupporting
confidence: 85%
See 1 more Smart Citation
“…Under low-to-moderate vegetation biomass cover (<5 kg m −2 vegetation water content), the L-band (1.4 GHz) Tb observations are especially sensitive to the dielectric properties, including moisture levels, within the surface soil layer (Entekhabi et al, 2010), which is congruent with the 0-to 5-cm surface soil layer depth of the SMAP L4SM product. This is also consistent with the L4C calibration against flux tower observations, as the surface soil layer generally encompasses more recent and labile SOC, which generally contributes the largest component of the soil RH flux (Bond-Lamberty et al, 2004) and is more sensitive to seasonal and interannual climate variability (Cagnarini et al, 2019;Chen et al, 2013) relative to deeper soil layers. The accuracy of L4SM soil moisture estimates is lower in areas of dense vegetation and areas where precipitation gauge measurements are sparse , due to uncertainty in the Tb assimilation and the Catchment land model, respectively.…”
Section: Data Sources 211 Smap L4c Surface Socsupporting
confidence: 85%
“…The role of microbial biomass in the stabilization and transformation of SOC is the most conspicuous missing piece of these models (Wieder et al, 2013), and, despite increasing global data availability (Crowther et al, 2019), it is perhaps the most difficult to parameterize for operational, global models. The emerging view of SOC dynamics emphasizes not just microbial functions but also substrate availability (Lehmann & Kleber, 2015; Luo et al, 2017) and the dynamic protection of mineral SOC that is partially dependent on soil texture and composition (Cagnarini et al, 2019). The quality and type of litter inputs as a function of the vegetation community is another missing piece (Hu et al, 2018) that affects the microbial influence on SOC dynamics but may be parameterized more easily than microbial functions in future models.…”
Section: Discussionmentioning
confidence: 99%
“…New hypotheses based on these findings posit that rapid cycling can still result in long-term SOM persistence, with mineral interactions temporarily slowing the flow of SOM rather than conferring permanent protection (Cagnarini et al, 2019). Empirical support for this hypothesis comes from recent high-resolution mass spectrometry work demonstrating that as dissolved organic C moves downward through the soil profile, its composition shifts toward mid-weight, saturated molecules with a high degradation index (Roth et al, 2019).…”
Section: Toward Dynamic Stabilitymentioning
confidence: 99%
“…Among these, topography is one of the five major soil surface formation factors (Jenny, 1994). Topography affects soil erosion and thus affects SOC's spatial distribution either directly or indirectly (Sun et al, 2010;Rodrigo-Comino et al, 2016Cagnarini et al, 2019;Cerdà and Rodrigo-Comino, 2020). Several studies have demonstrated the effects of topography and soil erosion on SOC's distribution (Beguería et al, 2015).…”
Section: Introductionmentioning
confidence: 99%